KEWENANGAN PENGADILAN NIAGA DALAM MEMUTUS PERKARA KEPAILITAN DENGAN KLAUSUL ARBITRASE - Apmayuda, Andrian; Firdaus, Firdaus; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
There are many ways in which business people can develop their business, there are people whocarry out large-scale promotions, open branches in different places, and so on. No small amount of money isneeded to develop the business. An alternative for business people to obtain sources of financing is byborrowing from different sources. The loan granted to the business actor by the lender and acting as adebtor is based on the assumption that the creditor believes that the debtor can pay the debt on time. if thereis a problem between the two parties regarding the agreement, this will be resolved through consultation. Ifno deliberation is reached, this will be resolved through an arbitration channel.Agreements between debtors and creditors often contain arbitration conditions. When a bankruptcydispute arises, which polemic arises which institution is authorized to resolve bankruptcy disputes, whetherthis is the commercial court or the arbitration body. The purpose of this essay, namely: first, to establish thebasis of authority of the commercial court to try bankruptcy cases related to the existence of arbitrationclause, secondly, to know the legal consequences of bankruptcy decisions of the commercial court withregard to the existence of arbitration clauses.Het type onderzoek dat wordt gebruikt bij het schrijven van deze wet is normatief juridischonderzoek. Door bibliotheekonderzoeksmethoden, gebruikte gegevensbronnen, primaire gegevens,secundaire gegevens en tertiaire gegevens te gebruiken, worden gegevensverzamelingstechnieken die in ditonderzoek zullen worden gebruikt, uitgevoerd door middel van literatuurstudies met daaropvolgendekwalitatieve analyse beschreven met en afgesloten met behulp van deductieve denkmethoden.Two important things can be concluded from the results of the study. First, if you pay attention to theagreement entered into by the parties through a link with the Civil Code (Article 1320 and Article 1338), thearbitration body has the authority to first settle the matter between PT. Fertilizer Indonesia and PT. SriMelamin Rejeki and the commercial court should not have the authority to check in advance, so the positionof the creditor must be determined in advance by an arbitration award. Secondly, the legal consequences ofbankruptcy decisions of the commercial court are related to the existence of arbitration clauses, namely thatthe arbitration body can continue the proceedings even though the parties to the commercial court haveargued because it was first bound by an arbitration clause according to the pacta sunt servanda inviteseveryone who makes it. The arbitration body may continue the dispute proceedings in the arbitration case,even if one of the parties has been declared bankrupt by the commercial courtKeyword: Autority - Commercial Court – Bankruptcy – Arbitration Clause